Tackling business model challenges in SME internationalization through digitalization - Wiebke Reim; Pirjo Yli-Viitala; Juha Arrasvuori; Vinit Parida (Journal of Innovation & Knowledge (JIK), 2022)
Many SMEs aim for business development by diversifying their offerings to fit global markets. However, internationalization has consequences for all aspects of a company's business model. Even though internationalization poses many business model challenges, the recent development of digital technology is a key enabler of resource-efficient internationalization and business development, an innovation that SMEs find accommodating. Thus, the purpose of this paper is to analyze how digitalization can help to surmount the business model challenges associated with SME internationalization. This paper builds on an exploratory case study of 29 SMEs who have an internationalization strategy and are from sparsely populated areas in Finland and Sweden. For the data analysis, the first-order codes of different business model challenges of SME internationalization have been merged into second-order themes. The final step of the analysis involved ascertaining the overarching dimensions of these business model challenges. This paper identifies business model challenges related to value creation, delivery, and capture throughout the internationalization process. In addition, a framework is developed that matches digitalization activities with the business model challenges. Because there is no 'one fits all' solution, this study matches specific digitalization activities with business model challenges that SMEs face when attempting to operate in international markets. These findings are important because they dissect digitalization into executable activities that SMEs find manageable.
Keywords: L; M; O; 650; Internationalization; SMEs; Value creation; Value capture; Business models; Digitalization